Short-term efficacy and safety of sintilimab combined with oxaliplatin and capecitabine as neoadjuvant therapy for locally advanced gastric cancer - ZHANG Shuai, LIU Liangliang, HUANG Di, SHENG Ru, DU Xuetao, LI Shuguang, HU Nan, ZHAO Yifeng (Zhongguo linchuang yanjiu)
Objective To investigate the short-term efficacy and safety of sintilimab combined with oxaliplatin and capecitabine(CapeOX) chemotherapy as neoadjuvant therapy for locally advanced gastric cancer. Methods From January 2019 to December 2020, 51 patients with locally advanced gastric cancer undergoing neoadjuvant therapy in the First Affiliated Hospital of Hebei North University were retrospectively analyzed. Twenty-four patients treated with sintilimab combined with CapeOX chemotherapy were the experimental group, and 27 patients treated with CapeOX chemotherapy were the control group. After evaluation, all patients underwent open or laparoscopic radical gastrectomy. Pathological tumor downstaging, tumor regression grade (TRG), pathological complete response rate (pCR) and major pathological response rate (MPR) were evaluated in the two groups, and adverse reactions were observed. Results The total downstaging rate of T stage and MPR in experimental group were higher than those in control group, but with no statistically significant difference (62.50%vs 40.74%,χ2= 2.407,P= 0.121; 25.00%vs 3.70%,χ2 3.231,P=0.072), while the total downstaging rate of N stage was significantly higher than that of control group (75.00%vs 37.03%,χ2 7.396,P=0.007). The experimental group surpassed the control group in evaluation of TRG (Z=2.444,P=0.015), among which 4 cases in the experimental group reached pCR(TRG 0 grade) and 0 case in the control group. There were no grade 4 adverse reactions occurred, and no significant difference was found in the incidence of adverse reactions between the two groups (P＞0.05). The incidence of immune-related adverse reactions in the experimental group was not high, and all of them were grade 1-2, which improved after symptomatic and supportive treatment. Conclusion Sintilimab combined with CapeOX chemotherapy as neoadjuvant therapy for patients with locally advanced gastric cancer can reduce the local tumor N stage, optimize the postoperative pathological TRG, which is conducive to improving the short-term efficacy of patients, and is safe and controllable.